Cost-effective communication network planning considering performance of pinning-based secondary control in microgrids. (December 2021) - Hu, Qian; Bu, Siqi; Li, Zilin; Zhou, Bowen; Yang, Dongsheng
Highlights: Pining synchronization protocols for distributed secondary control in microgrid. Impact analysis of communication topology using spectral graph properties. Development of critical algebraic connectivity constraint for communication network. Communication network planning model based on Mixed Integer Semidefinite Program. Problem relaxation using Linear Matrix Inequalities and KKT conditions. Abstract: Driven by the fact that the structural topology of the communication network has a significant effect on the dynamical performance of the related physical network, this paper addresses the communication network planning problem for islanded microgrids (MGs). The optimal communication topology with the lowest communication cost, which supports the desired performance of pinning-based distributed control is designed in the MG planning stage. To achieve that, firstly, pinning synchronization control (PSC) is developed to regulate the voltage and frequency at each distributed generator (DG) to the reference state. Then criteria of the algebraic connectivity of communication network to fulfill the convergence requirement of PSC protocols are derived analytically using spectral graph properties and Lyapunov theory. A communication network planning model is formulated as Mixed Integer Semidefinite Program (MISDP) by using Linear Matrix Inequalities (LMI) techniques. The convergence speed requirement of PSC, communication time delay and the importance of connections between DGs are considered as constraints. The optimal communication network with the lowest communication cost can be acquired and meanwhile the satisfactory dynamical performance of PSC protocols can be guaranteed. The case studies are designed to evaluate how the planning model can practically facilitate the pinning-based control in the islanded MG. The simulation results effectively verify that the dynamical control convergence can be improved under the properly designed communication network. The control performance of the proposed protocol is validated experimentally based on a two-DG MG prototype.